Well I ll be dammed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Large dams generate 19% of global electricity production, provide water for 12 to 16% of world food production, and have displaced between 40 and 80 million people. Their role should be better restricted and channelled. In the future, all...